1996
DOI: 10.1046/j.1475-1313.1996.95000089.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of spectacle and contact lens wear in the UK fire service

Abstract: Despite the fact that firefighting has been shown to be a visually demanding occupation, the present visual standards for firefighters prohibit the use of spectacles or contact lenses operationally. To determine the proportion of the UK fire service currently using spectacles and contact lenses, and how many may benefit from optical correction, a questionnaire was distributed. This contained 30 questions and was sent to 1550 firefighters. The data from 1064 returned questionnaires have been analysed. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In 1988, the Agency published an enforcement procedure allowing the use of rigid gas-permeable and soft contact lenses in all workplaces and with all types of respirators. 9 Subsequent studies and review articles have confirmed the safety and efficacy of appropriate use of both soft contact lens and/or rigid gas permeable contact lens in the workplace, [10][11][12][13] and in fact the use of contact lenses for vision correction may be advantageous in the workplace.…”
mentioning
confidence: 96%
“…In 1988, the Agency published an enforcement procedure allowing the use of rigid gas-permeable and soft contact lenses in all workplaces and with all types of respirators. 9 Subsequent studies and review articles have confirmed the safety and efficacy of appropriate use of both soft contact lens and/or rigid gas permeable contact lens in the workplace, [10][11][12][13] and in fact the use of contact lenses for vision correction may be advantageous in the workplace.…”
mentioning
confidence: 96%